A Simple, reversed-phase Ultra performance liquid chromatographic method for the simultaneous determination of Monocrotophos, Thiram, carbendazim, Carbaryl and imidacloprid pesticides by Quechers method in chilli samples. - Bilehal, Dinesh C; Chetti, M B; Goroji, P T; Khethagoudar, Mahadev C (International Multidisciplinary Research Journal, 2012)
A simple, reversed-phase Ultra-performance liquid chromatographic (RP-UPLC) method for the simultaneous determination of five pesticides namely Monocrotophos, Thiram, Carbendazim, Carbaryl and Imidacloprid has been developed. This method involves sample preparation by QueCherS method and quantification by ultra performance liquid chromatography with tunable dual wavelength detector. The mobile phase composition was varied to improve peak resolution and peak sensitivity. Choosing the match between the stationary phase and mobile phase composition, the developed RP-UPLC method not only can simplify the procedure but also significantly reduce the analysis time. The method presents an average recovery of 87.9% and 96.9%, in repeatability and intermediate precision conditions, respectively, with adequate precision (RSD from 0.8 to 20.7%), for all compounds. The method was applied to determine these pesticide residues in chilli samples.